Analisis ketenagakerjaan penduduk lanjut usia (studi kasus pensiunan guru pegawai negeri sipil) di kota samarinda (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
An increase in the proportion of the elderly population is one of the demographic trends currently seen. This research aims to describe and analyze about employment of the elderly population, especially the elderly population who are civil servant teachers who will retire and retire. This reseaarch uses qualitative approach, and descriptive as a reseach design. The location of this research is in Samarinda. Determination of informants using purposive sampling technique. After the data have collected, it will be analyzed to get the conclusion, in testing the validity of the data using triangulation techniques with sources. The result of this research shows that there are some reasons that make the elderly population who are civil servant teachers who will retire and who have retired decide to continue working, fulfilling their daily needs, having dependents on family members, healthy and including filling their time.